2017
DOI: 10.1556/606.2017.12.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Hygrothermal simulations and In-situ measurements of ultra-lightweight concrete panels

Abstract: The aim of the paper is to investigate the hygrothermal properties of a newly developed building panel, made of ultra-lightweight concrete, encased cold-formed steel elements. It describes the hygrothermal simulations of the wall and roof panels, and based on results, the heat transfer coefficients and linear thermal transmittances are determined. The hygrothermal behavior of main structural joints (wall corner, wall-roof and wall-ground connections) is also simulated using real indoor and outdoor conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For the other materials, data were not available from the manufacturer; thus, the conductivity reported in a previous study [31] was used. In previous studies [45][46][47][48], the conductivity of a material changed with temperature and moisture content, affecting the U-value of the wall; however, this was not considered in this study. Many previous studies also utilized the conventional surface resistance values given in ISO 6946 [1] to calculate the theoretical U-value of walls.…”
Section: Test Wallmentioning
confidence: 96%
See 1 more Smart Citation
“…For the other materials, data were not available from the manufacturer; thus, the conductivity reported in a previous study [31] was used. In previous studies [45][46][47][48], the conductivity of a material changed with temperature and moisture content, affecting the U-value of the wall; however, this was not considered in this study. Many previous studies also utilized the conventional surface resistance values given in ISO 6946 [1] to calculate the theoretical U-value of walls.…”
Section: Test Wallmentioning
confidence: 96%
“…In addition to the aforementioned factors, the discrepancies between theoretical and measured values are also influenced by the nature of the wall, method of analysis, quality of construction, age of the material, and inaccurate thermophysical properties of the material. Recently, several studies have shown that the application of surface resistances that differ from onsite measurements [40][41][42][43][44] and changes in the conductivity of materials due to temperature and moisture [45][46][47][48] can be the main causes of discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, out of 340 publications listed on the website of WUFI, there are only 22 English language papers dealing with the 2D analysis of building constructions. The possibility of creating multidimensional simulations by using commercial software started in 2000 when the Fraunhofer Institute presented the WUFI 2D [15] with many applications since then [16], [17]. Besides WUFI, there are other available tools, such as Comsol Multiphysics, which is also capable of performing conjugated heat and moisture transport simulations according to EN 15026 [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A new addition to the documents related to in-situ measurement of thermal resistance of building partitions is the ISO 9869-2 standard, which introduces the infrared camera method [ 28 ]. In issues related to heat transfer through building partitions and the determination of their thermal resistance, a very important issue is to take into account the variability of material moisture and its transfer [ 29 , 30 ]. However, this research problem was not within the scope of this article.…”
Section: Introductionmentioning
confidence: 99%